Curcumin as a Cancer Nutraceutical Candidate: Systematic Review of Preclinical Antiproliferative, Anti-Metastatic, and Formulation Evidence - Resti Zulhaijah; Subandi Subandi; Loeki Enggar Fitri (Journal of Nutrition Explorations, 2026)
Curcumin, a polyphenolic constituent of turmeric (Curcuma longa), has been investigated as a food-derived nutraceutical with potential anticancer properties, although clinical translation remains limited by poor aqueous solubility, chemical instability, rapid metabolism, and low systemic exposure. This systematic review, conducted in accordance with the PRISMA 2020 statement, evaluated whether native or formulated curcumin, compared with untreated or vehicle controls, exerts antiproliferative and anti-metastatic effects in cancer cell lines, 3D models, or tumor-bearing animal models. Studies on synthetic curcumin analogs, undefined turmeric extracts, and multi-phytochemical combinations were excluded. The protocol was submitted for PROSPERO registration. A systematic search of PubMed/MEDLINE, Scopus, ScienceDirect, and SpringerLink from January 2016 to 20 June 2026 identified 15 eligible studies: nine investigating native curcumin and six investigating formulated curcumin. Across breast, ovarian, colorectal, thyroid, pancreatic, hepatocellular, and meningioma models, curcumin generally reduced cancer-cell viability, proliferation, migration, invasion, epithelial–mesenchymal transition, and tumor growth, mainly through pathways governing cell survival, signal transduction, and metastatic behavior. Ten studies (67%) were exclusively in vitro, while five (33%) included in vivo or xenograft components. Formulated curcumin studies showed that anticancer performance depended on carrier type: an ionic-liquid system increased aqueous solubility by approximately 8,750-fold and reduced MDA-MB-231 viability by about 60% at 10 µg/mL without comparable toxicity in normal fibroblasts, curcumin nanocapsules showed a lower IC₅₀ than microcapsules in breast cancer cells, and curcumin spanlastics produced stronger anticancer activity than nanocrystals, which instead showed the most rapid dissolution. Overall, curcumin demonstrated promising preclinical bioactivity, but the evidence remained limited by substantial heterogeneity in models, formulations, doses, exposure durations, and outcome measures, which precluded meta-analysis. These findings support curcumin as a biologically active nutraceutical candidate requiring further pharmacokinetic, safety, and in vivo validation before translational application in cancer care.